Volumetric modulated arc therapy total body irradiation improves toxicity outcomes compared to 2D total body irradiation - Hui, Caressa; Simiele, Eric; Lozko, Yuliia; Romero, Ignacio; Skinner, Lawrie; Binkley, Michael Sargent; Hoppe, Richard; Kovalchuk, Nataliya; Hiniker, Susan M. (Frontiers in Oncology, 2024)
IntroductionVolumetric modulated arc therapy (VMAT) total body irradiation (TBI) allows for greater organ sparing with improved target coverage compared to 2D-TBI. However, there is limited evidence of whether improved organ sparing translates to decreases in toxicities and how its toxicities compare to those of the 2D technique. We aimed to compare differences in toxicities among patients treated with TBI utilizing VMAT and 2D techniques.Methods/materialsA matched-pair single-institution retrospective analysis of 200 patients treated with TBI from 2014 to 2023 was performed. Overall survival (OS) and progression-free survival (PFS) were analyzed using the Kaplan–Meier method and compared using log-rank tests. Differences in characteristics and toxicities between the VMAT and 2D cohorts were compared using Fisher’s exact test.ResultsOf the 200 patients analyzed, 100 underwent VMAT-TBI, and 100 underwent 2D-TBI. The median age for VMAT-TBI and 2D-TBI patients was 13.7 years and 16.2 years, respectively (p = 0.25). In each cohort, 53 patients were treated with myeloablative regimens (8–13.76 Gy), and 47 were treated with non-myeloablative regimens (2–4 Gy). For the entire VMAT-TBI cohort, lung Dmean, kidney Dmean, and lens Dmax were spared to 60.6% ± 5.0%, 71.0% ± 8.5%, and 90.1% ± 3.5% of prescription, respectively. For the non-myeloablative VMAT-TBI cohort, testis/ovary Dmax, brain, and thyroid Dmean were spared to 33.4% ± 7.3%, 75.4% ± 7.0%, and 76.1% ± 10.5%, respectively. For 2D-TBI, lungs were spared using partial-transmission lung blocks for myeloablative regimens. The VMAT-TBI cohort experienced significantly lower rates of any grade of pneumonitis (2% vs. 12%), nephrotoxicity (7% vs. 34%), nausea (68% vs. 81%), skin (16% vs. 35%), and graft versus host disease (GVHD) (42% vs. 62%) compared to 2D-TBI patients. For myeloablative regimen patients, rates of pneumonitis (0% vs. 17%) and nephrotoxicity (9% vs. 36%) were significantly lower with VMAT-TBI versus 2D-TBI (p < 0.01). Median follow-up was 14.3 months, and neither median OS nor PFS for the entire cohort was reached. In the VMAT versus 2D-TBI cohort, the 1-year OS was 86.0% versus 83.0% (p = 0.26), and the 1-year PFS was 86.6% and 80.0% (p = 0.36), respectively.ConclusionNormal tissue sparing with VMAT-TBI compared to the 2D-TBI translated to significantly lower rates of pneumonitis, renal toxicity, nausea, skin toxicity, and GVHD in patients, while maintaining excellent disease control.